(3GdHOjYI GdMRQjI HGdYbhO GdLhgQjIs - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj,J (B1143 (3g` s
(3ChdgG (B:s
(3jG MSf eWdY ef Cghi HPi Sde HQGYI GdThb ai GSJgdGdgG Cde jG efRd GdQcH Hjf GdHGf aGdYde ef SaM cGXeI MjjJ HGdOje s
(3BNQgG (B:s
(3ai GdHjJ GdSghdI , hbO CONdgG HYVge ai fhY GdGfSLGe hGdUhGH CfgG ZjQg heKdg dHgGA GdOjf RgjQg aEfg MeGeI gPG GdOhM ajef bWY GdehOI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B32 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B593s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeYgO GdehQjJGfi ddHMK GdYdei (B((3COH (B: (3eOjM fHhi (B1759) s
Keywords: (3GdCOHs